Inflation and output dynamics in a model with labor market search and capital accumulation - Burkhard Heer; Alfred Maußner (Center for Economic Studies and ifo Institute (CESifo), 2007)
In a sticky-price model with labor market search and habit persistence, Walsh (2005) shows that inertia in the interest rate policy helps to reconcile the inflation and output persistence with empirical observations for the US economy. We show that this finding is sensitive with regard to the introduction of capital formation. While we are able to replicate the findings for the inflation inertia in a model with capital adjustment costs and variable capacity utilization, the output response to an interest shock is found to be too large and no longer hump-shaped in this case. In addition we find that the response of output to a technology shock can only be reconciled with empirical findings if either the adjustment of the utilization rate is very costly or there is only a modest amount of nominal rigidity in the economy.
Keywords: E52; E32; J64; 330; Zinspolitik; Schock; Gesamtwirtschaftliche Produktion; Konjunktur; Inflation; Arbeitsplatzsuchmodell; Preisrigidität; Theorie